The Dermatophyte Trichophyton rubrum Induces Neutrophil Extracellular Traps Release by Human Neutrophils - Reis, Ana Paula Carvalho (2022)
Neutrophils are the first leukocytes recruited to the site of infection and are thought to be responsible for fungal elimination from the skin such as dermatophytes. Neutrophils are able to secrete reactive oxygen species (ROS) and neutrophil extracellular traps (NETs) that can kill different fungi, including Aspergillus, spp., Candida albicans, and Phialophora verrucosa. However, NET production in response to Trichophyton rubrum, the main etiologic agent of dermatophytosis, has yet to be studied. We demonstrated that human neutrophils produce NETs against different morphotypes of T. rubrum in a dose-dependent manner and NET formation is dependent on ROS production. In addition, ROS production by human neutrophils in response to T. rubrum is dependent on NADPH oxidase, but not on fungal viability. NETs mediated killing of T. rubrum. Collectively, these results demonstrate that T. rubrum was able to trigger the production of NETs, suggesting that these extracellular structures may represent an important innate immune effector mechanism controlling physiological response to T. rubrum infection.